Compaction behaviour of Moringa oleifera leaves powder by fitting into compression models - Ali, M. A.; Yusof, Yus Aniza; Chin, Nyuk Ling; Ibrahim, N. M. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Moringa oleifera has an impressive range of therapeutic uses with high concentration of vitamins, minerals and amino acids. The present study determined the behaviour of pure Moringa leaves powder with reference to a most commonly used universal binder that is Microcrystalline Cellulose (MCC) in pharmaceutical industry. A uni-axial die compaction technique was used to compact the powders. Tablet size (diameter) and weight for both powders were kept constant as 13 mm diameter and 500±5 mg, respectively. The applied pressure ranging from 37.6 MPa to 188 MPa with a plunger speed of 0.01 mm/sec. A tangential compression test was done to calculate tensile strength of tablets. For further understanding of data, compression models included Kawakita and Lüdde, Heckle, Adams and Panelli-Filho models were fitted. As a result, Kawakita and Lüdde model was best fitted as compare to other three models. The flowability and tensile strength of pure Moringa leaves powder was very poor and extremely low, respectively as compare to microcrystalline cellulose. Thus, this approach can be applied for fundamental understanding of Moringa oleifera leaves powder in solid form like tablet.